2013
DOI: 10.1371/journal.pone.0082471
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling of Primary Cutaneous Large B-Cell Lymphomas

Abstract: Aberrant expression of microRNAs is widely accepted to be pathogenetically involved in nodal diffuse large B-cell lymphomas (DLBCLs). However, the microRNAs profiles of primary cutaneous large B-cell lymphomas (PCLBCLs) are not yet described. Its two main subtypes, i.e., primary cutaneous diffuse large B-cell lymphoma, leg type (PCLBCL-LT) and primary cutaneous follicle center lymphoma (PCFCL) are characterized by an activated B-cell (ABC)-genotype and a germinal center B-cell (GCB)-genotype, respectively. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In the only other study on miRs in PCLBCL-LT and PCFCL, using a different methodology based on miR profiling with high-throughput sequencing, the authors found miR-106a among the 30 miRs most abundantly expressed in 19 cutaneous B-cell lymphomas, in accordance with our results (Koens et al, 2013). When they compared PCLBCL-LT and PCFCL samples using single quantitative real-time reversetranscriptase-PCR, they found miR-9-5p, miR-31-5-p, miR129-2-3p, and miR-214-3p underexpressed in PCFCL.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the only other study on miRs in PCLBCL-LT and PCFCL, using a different methodology based on miR profiling with high-throughput sequencing, the authors found miR-106a among the 30 miRs most abundantly expressed in 19 cutaneous B-cell lymphomas, in accordance with our results (Koens et al, 2013). When they compared PCLBCL-LT and PCFCL samples using single quantitative real-time reversetranscriptase-PCR, they found miR-9-5p, miR-31-5-p, miR129-2-3p, and miR-214-3p underexpressed in PCFCL.…”
Section: Discussionsupporting
confidence: 90%
“…In this molecular and bioinformatics study performed on skin biopsy samples from 44 patients with cutaneous B-cell lymphomas, we found an overexpression of all the miRs of the oncogenic miR-17-92 cluster in cutaneous lymphomas compared with normal skin, whereas miR-92 was overexpressed in cutaneous lymphomas compared with reactive lymph node. In the pilot study by Koens et al (2013), 3 of these miRs had also been identified in the 30 most abundantly expressed miRs in 19 PCLBCL-LT and PCFCL. Experimental data have deciphered the function of miR-17-92 cluster in lymphomas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, different mature forms of miR-129 display diverse expressions. Single microRNA RT-qPCR was conducted on ormalin-fixed paraffin-embedded tumor biopsies, confirming higher expression of miR-129-2-3p and in PCFCL as compared to PCLBCL-LT [27]. Yu et al reported that miR-129-1-3p, miR-129-2-3p, and miR-129-5p expression levels in gastric cancer cells were significantly 5p was significantly upregulated in the serum of acute myeloid leukemia (AML) patients compared with normal controls and underexpressed in human hematopoietic stem cells, with EIF2C3 and CAMTA1 identified as its targets, suggesting that miR-129-5p may act an important role in the genesis of AML [31].…”
Section: The Roles Of Mir-129 In Human Cancersmentioning
confidence: 83%
“…It is involved in the differentiation of B lymphocytes into plasma cells by the negative regulation of the transcription factor PR domain zinc finger protein 1 (PRDM1/BLIMP-1), showing lower levels as the lymphocytes differentiate. This explains high levels of miR-9-5p in primary large-B cell lymphomas [42]. On the other hand, miR-9 is downregulated in human ovarian cancer compared with normal ovary, and the overexpression of miR-9 inhibits cell growth in ovarian cancer in vitro through the negative regulation of nuclear factor NF-kappa-B p105 (NFκB1) [42,43].…”
Section: Discussionmentioning
confidence: 99%